Cross-sectional, quantitative analysis of motor function in females with HNRNPH2-related disorder. (December 2021) - Salazar, Rachel; Beenders, Sara; LaMarca, Nicole M.; Thornburg, Olivia; Rubin-Thompson, Lewis; Snow, Arielle; Goldman, Sylvie; Chung, Wendy K.; Bain, Jennifer M.
Highlights: HNRNPH2- related neurodevelopmental disorder has quantifiable motor impairment. The GMFM-88 and PEDI-CAT scores validly quantifies motor abilities. Motor function is accurately assessed by caregivers of individuals with HNRNPH2 . Abstract: Aims: To describe the gross motor function of individuals with HNRNPH2 -related disorder (OMIM 300986, Mental Retardation, X-linked, Syndrome, Bain Type; MRXSB) and determine the associations between clinician-measured motor function and caregiver-reported mobility scores. Methods: Developmental histories of 17 female participants with HNRNPH2 -related disorder (mean age 11.2 years, range 2.7–37.1 years) with various genotypes within and adjacent to the nuclear localization sequence (NLS) were analyzed. Participants performed the Gross Motor Function Measure-88 (GMFM-88) and caregivers completed developmental histories and the Pediatric Evaluation of Disability Inventory-Computer Adaptive Test (PEDI-CAT). Results: All participants had measurable and quantifiable motor impairments. A strong positive correlation between the clinician-measured GMFM-88 total score and the caregiver-reported PEDI-CAT mobility domain score was established. Motor deficits were noted more often in individuals who were nonverbal. The 2 participants with genotypes adjacent to the NLS appear to have milder motor phenotypes. Conclusions: The GMFM-88 and PEDI-CAT are useful and feasible measures of mobility in individuals with HNRNPH2 -related disorders. Convergent validity was established between the clinician-measured GMFM-88 raw scores and caregiver-reported PEDI-CAT mobility domain scores. Factors including verbal status and genotype may impact motor abilities.